The works of Cornelius Tacitus / by Arthur Murphy ; with an essay on the life and genius of Tacitus, notes, supplements, and maps. - Tacitus, Cornelius. (Tufts University. Tisch Library., 2016)
Volume 1 of 4.; 1 online resource (4 volumes, plates) : maps.; "In four volumes."; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Indexed in: English Short Title Catalog,T96047